A comparison of the effects of apigenin and seven of its derivatives on selected biomarkers of oxidative stress and coagulation in vitro. (February 2020) - Kowalska, Iwona; Adach, Weronika; Stochmal, Anna; Olas, Beata
Abstract: Apigenin is a phenolic compound widely present in many fruits, vegetables and herbs. Its name originates from Apium : a genus of the Apiaceae. The aim of the present study was to determine the antioxidant or pro-oxidant properties of apigenin and seven of its derivatives, isolated from the aerial parts of barrel medic ( Medicago truncatula ) and common wheat ( Triticum aestivum ), in human plasma treated with a hydroxyl radical donor (OH ) in vitro . It also examines their influence on the parameters of coagulation. The compounds were found to demonstrate different effects on oxidative stress and coagulation which may be related to differences in their structure. In particular, apigenin 7-O-{2′-O-feruloyl-[ β -D-glucuronopyranosyl(1 → 3)]- β -D- glucuronopyranosyl(1 → 2)-O- β -D-glucopyranoside} demonstrates both antioxidant and anticoagulant activities, and may offer the most promise for the prevention and treatment of cardiovascular disorders of all the phenolic compounds tested so far. Graphical abstract: Image 1